1986
DOI: 10.1007/bf00446369
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine acetyltransferase in pea cotyledon mitochondria

Abstract: Purified pea cotyledon mitochondria did not oxidise acetyl-CoA in the presence of carnitine. However, acetylcarnitine was oxidised. It was concluded that acetylcarnitine passed through the mitochondrial membrane barrier but acetyl-CoA did not. Only a sensitive radioactive assay detected carnitine acetyltransferase in intact mitochondrion or intact mitoplast preparations. When the mitochondria or mitoplasts were burst, acetyl-CoA substrate was available to the matrix carnitine acetyltransferase and a high activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Overall, our observations imply that ACL is near-limiting in generating cytosolic acetyl-CoA and that other mechanisms (Wood et al, 1983;Burgess and Thomas, 1986;Masterson et al, 1990) for generating cytosolic acetyl-CoA cannot substitute for ACL-derived acetyl-CoA.…”
Section: Acl-derived Acetyl-coa Is Nonredundant In Cytosolic Acetyl-cmentioning
confidence: 65%
See 1 more Smart Citation
“…Overall, our observations imply that ACL is near-limiting in generating cytosolic acetyl-CoA and that other mechanisms (Wood et al, 1983;Burgess and Thomas, 1986;Masterson et al, 1990) for generating cytosolic acetyl-CoA cannot substitute for ACL-derived acetyl-CoA.…”
Section: Acl-derived Acetyl-coa Is Nonredundant In Cytosolic Acetyl-cmentioning
confidence: 65%
“…By distributing this metabolism among separate cellular and subcellular compartments, plants have the potential of simplifying the regulatory processes that control this complex network. Although the generation of plastidic acetyl-CoA as the precursor for fatty acid biosynthesis has been the focus of considerable research (Millerd and Bonner, 1954;Nelson and Rinne, 1975;Reid et al, 1975;Kuhn et al, 1981;Kaethner and ap Rees, 1985;Burgess and Thomas, 1986;op den Camp and Kuhlemeier, 1997;Ke et al, 2000;Schwender and Ohlrogge, 2002), few studies have directly addressed the question of how the cytosolic (Kaethner and ap Rees, 1985;Fatland et al, 2002;Schwender and Ohlrogge, 2002) or nuclear acetyl-CoA pools are generated. This is despite the fact that most of the chemical diversity of acetate-derived molecules is generated from the cytosolic acetyl-CoA pool.…”
Section: Discussionmentioning
confidence: 99%
“…This acetate could be synthesized in the mitochondria by the combined action of mtPDC and an acetyl-COA hydrolase (Murphy and Stumpf, 1981;Zeiher and Randall, 1990). Also, acetyl-COA could be shuttled directly between the mitochondria and chloroplasts by a camitine/acetyl camitine exchange system across the mitochondrial (Burgess and Thomas, 1986) and chloroplast (McLaren et al, 1985) inner membranes. The low mtPDC to cpPDC capacity found in barley leaves raises the question of whether enough acetyl-COA is produced by mtPDC to provide substrate for both CS and a possible acetyl-COA hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…It is suprising that Roughan et al (1993) found no CAT activity in homogenates of pea shoots and spinach and amaranthus leaves as it is fairly well established that mitochondria at least possess CAT activity Wood et al 1983;Burgess & Thomas 1986;Gerbling & Gerhardt 1988;Budde et al 1991) and this mitochondrial CAT should have been detected.…”
Section: Discussionmentioning
confidence: 99%